5th National Congress of the Italian Society of Physiotherapy. Issue 1 (October 2016) - Aina, Alessandro; Barbero, Marco; Cagnie, Barbara; Castelli, Elena; Cook, Chad; Ferrari, Silvano; Foglia, Andrea; Bizzarri, Paolo; Giraudo, Donatella; Littlewood, Chris; Pillastrini, Paolo; Piscitelli, Daniele; et al.
Table of contents S1 Criteria for exercises selection in subjects with low back pain Alessandro Aina S2 Recent advances in pathophysiology and treatment of myofascial trigger points Marco Barbero S3 Rehabilitation of scapular dyskinesia Barbara Cagnie S4 Musculoskeletal rehabilitation in subjects affected by neurological disorders Elena Castelli S5 Which examination tests suggest the best candidates for manual therapy Chad Cook S6 Case study: the role of the measurements for the identification of targets and guidance of the treatment Silvano Ferrari S7 Assessment of joint mobility: state of the art Andrea Foglia, Paolo Bizzarri S8 Core stabilization exercises in the treatment of urinary incontinence Donatella Giraudo S9 Preventing surgical subacromial decompression through rotator cuff rehabilitation Chris Littlewood S10 Methodological aspects of Clinical Prediction Rules in the rehabilitation of Low Back Pain Paolo Pillastrini S11 Interpretability of outcome measures in musculoskeletal rehabilitation Daniele Piscitelli S12 Conservative treatment of the misalignment of the spine: state of the art and perspectives Michele Romano S13 Balance training in subjects with musculoskeletal disorders Andrea Tettamanti S14 Dosage of manual therapy: principles for clinical practice Carla Vanti S15 Are there speed limits in post-surgery lower limb rehabilitation? Stefano Vercelli S16 Classification of predominant neuropathic, nociceptive or central sensation pain Lennard Voogt P1 A wearable proprioceptive stabilizer (Equistasi®) for rehabilitation of balance disorders in multiple sclerosis patients: preliminary results of a randomized, double-blind, versus placebo controlled study Aceto Maria, Spina Emanuele, Paone Paolo, Silvestre Francesco, Carotenuto Antonio, Cerillo Ilaria, Orefice Giuseppe P2 Effect of repeated neck retraction movements on strength and EMG activity of the upper limbs, range of motion and cervical posture Bassi Raffaele, Fiorito Serena, Aina Alessandro P3 Hamstring injuries: clinical assessment or image evaluation? Bonfanti M., Pasquetti M. P4 Effectiveness of the physical therapy treatment on pelvic floor muscles in pelvic girdle pain. A literature review Bortolami Arianna, Pillastrini Paolo, Vanti Carla P5 Scapulo-humeral muscles electromiographic activity during the elevation movement of the upper limb in subjects with rotator cuff lesion Brioschi D, Vitali M, Pedretti A, Fraschini G, Tettamanti A P6 Mechanical low back pain: secular trend and intervention topics of randomized controlled trials Castellini G, Gianola S, Bonovas S, Banfi G, Moja L P7 Quality of reporting in rehabilitation interventions for low back pain: a review of published randomised controlled trials Greta Castellini, Silvia Gianola, Pamela Frigerio, Michela Agostini, Rosa Bolotta, Davide Corbetta, Monica Gasparini, Paolo Gozzer, Erica Guariento, Linda Li, Valentina Pecoraro, Valeria Sirtori, Andrea Turolla, Andreano A, Lorenzo Moja P8 Power analysis and sample size reporting in rehabilitation of low back pain: review of randomized controlled trials included in Cochrane systematic review Castellini G, Gianola S, Bonovas S, Moja L P9 A core outcome set for clinical trials in non-specific low back pain Alessandro Chiarotto, Caroline B. Terwee, Maarten Boers, Raymond W. Ostelo P10 Roland & Morris Disability Questionnaire and Oswestry Disability Index: which has better measurement properties? A systematic review and meta-analysis Alessandro Chiarotto, Lara J. Maxwell, Caroline B. Terwee, George A. Wells, Peter Tugwell, Raymond W. Ostelo P11 Prevalence of myofascial trigger points in spinal pain disorders: systematic review and meta-analysis Alessandro Chiarotto, Ron Clijsen, Cesar Fernandez-de-las-Penas, Marco Barbero P12 Post-surgical scar rating scales in physiotherapy: a systematic review Ciceri Matteo, Rossetti Sara, Vercelli Stefano P13 Efficacy of action observation pre-operative training in functional recovery after hip and knee prosthesis Cislaghi M, Penone G, Marinelli G, Rezzan G, Melegati G, Gatti R P14 The use of Kinesio Taping in the treatment of hematomas: can we distinguish fancy from the effects? Colombo Claudio, Tolosa Francesca, Andrea Moriondo, Vercelli Stefano P15 Who is able to perform explicit motor imagery after stroke? Stefano Doronzio, Matteo Paci P16 Responsiveness of the Bridge tests in Symptomatic Lumbar Spondylolisthesis Silvano Ferrari, Carla Vanti, Marco Monticone P17 The relationship between number of sessions and clinical results in lumbar symptomatic spondylolisthesis Silvano Ferrari, Carla Vanti, Marco Monticone P18 Conservative treatments for upper extremity tendinopathies in occupational medicine: narrative review Garzonio Fabiola, Zanetta Anna, Bargeri Serena, Cerone Giorgia, Sartorio Francesco P19 The time-related effect of roller-massager on extensibility of the hamstring muscles Filippo Ghirlanda, Alessandro Schneebeli, Corrado Cescon, Marco Barbero P20 Effect of two different exercise programs on pain, disability and quality of life in people with subacute and chronic nonspecific neck pain Gioia G, Faccendini S, Aina A, Tettamanti A P21 A bridge between clinical practice and research: how health professionals can study literature and learn on the job Granzotto G, Coppola L, Gava I, Frassinelli M, Gattinoni F P22 Walking capacity improves after neuromotor physiotherapy in stroke patients Lorenzo Guidotti, Marco Postiglione, Bruna Lombardi, Matteo Paci P23 Intra and inter-session reliability of the angle between pain onset and submaximal pain during upper limb neurodynamics test 1: a study in healty individuals Diego Leoni, Davide Storer, Roberto Gatti, Michele Egloff, Marco Barbero P24 Effects of an AO-MI training on balance task in patients affected by multiple sclerosis Magno Tiziano, Tettamanti Andrea P25 Outcomes of treatment with neuromuscular stimulator for chronic anterior knee pain: a clinical case Daniele Maremmani, Sebastiano Cencini, Giuseppe Plebani P26 Consistency in locating pressure stimuli over the lumbar spine on a digital body chart: a comparison between chronic low back pain patients and healthy subjects Federica Moresi, Marco Barbero, Matteo Isnardi, Alberto Gallace, Corrado Cescon, Roberto Gatti P27 Malignant Cord Compression in the thoraco-lumbar spine. Early signs and symptoms in the differential diagnosis of low back pain Moretti N, Maselli, Testa M. P28 End growth results of exercise treatment to avoid bracing in adolescents with idiopathic scoliosis: a prospective cohort controlled study Stefano Negrini, Sabrina Donzelli, Francesco Saveri, Alessandra Negrini, Silvana Parzini, Michele Romano, Fabio Zaina P29 Reliability of the Ashworth scale and its modified versions: systematic review and meta-analysis Leonardo Nesi, Francesco Ferrarello, Valeria Anna Maria Bianchi, Matteo Paci P30 Differences in motor recovery between upper and lower limbs in stroke subtypes Matteo Paci, Luca Nannetti, Bruna Lombardi P31 Influence of clinical experience on the reliability of the Salford Gait Tool Giuditta Mini, Mariangela Marchettini, Francesco Ferrarello, Matteo Paci P32 A somatosensory discrimination training induces brain functional changes in healthy young subjects Fabio Piccolo, Federica Agosta, Elisabetta Sarasso, Paola Adamo, Federico Temporiti, Andrea Falini, Roberto Gatti, Massimo Filippi P33 Effects of dynamic tilt-table with integrated robotic stepping associated with functional electrical stimulation: a cross-over study Daniele Piscitelli, Roberto Meroni, Leonardo Pellicciari, Marco A. Mondelli, Thomas Favaron, Cesare G. Cerri, Enrico A. Tallarita P34 Manual therapy techniques in the treatment of whiplash and its associated disorders: a systematic review Ravizzotti Elisa, Vercelli Stefano P35 The Patient and Observer Scar Assessment Scale (POSAS) as a screening tool for early detection of pathologic post-surgical scars in physiotherapy Rossetti Sara, Ciceri Matteo, Vercelli Stefano P36 The anatomical basis of genetic dystonia: a multimodal MRI study Elisabetta Sarasso, Federica Agosta, Aleksandra Tomić, Silvia Basaia, Nataša Dragašević, Marina Svetel, Massimiliano Copetti, Vladimir S. Kostic, Massimo Filippi P37 The relative inclination of the end vertebrae of a scoliotic single curve can influence the results of the conservative treatment? A pilot study Francesco Saveri, Michele Romano, Matteo Mastrantonio, Alessandra Negrini, Fabio Zaina, Negrini Stefano P38 Physiotherapy for myofascial pain syndromes: reported methodological quality of randomized controlled trials indexed in the PEDro database Alessandro Schneebeli, Greta Castellini, Valentina Redaelli, Emiliano Soldini, Marco Barbero P39 Is the patellar pubic percussion test useful to diagnose only femur fractures or something else? Two case reports Segat M, Casonato O, Margelli M, Pillon S. P40 Effectiveness of new rehab method for MDI Spunton V, Fenini R, Garofalo R, Conti M P41 Toe walking and autism: cross-sectional study on clinical presentation patterns and correlation with language delay Valagussa G, Balatti V, Trentin L, Melli S, Norsi M, and Grossi E P42 Active Kyphosis Value (AKV): a new test for the evaluation of the kyphotisation mobility of the thoracic spine Massimiliano Vanossi, Francesco Saveri, Michele Romano P43 Pain Drawing and psychological distress in low back pain - systematic review and meta-analysis Carla Vanti, Sara Taioli, Ivan Gardenghi, Lucia Bertozzi, Anna Rosso, Antonio Romeo, Paolo Pillastrini P44 Responsiveness of the Oswestry Disability Index in symptomatic lumbar spondylolisthesis Carla Vanti, Silvano Ferrari, Martina Ruggeri, Marco Monticone P45 The relationship between instability tests, pain and disability in non-specific low back pain Carla Vanti, Bellini Filippo, Cristina Conti, Federica Faresin, Martina Ruggeri, Raffaella Piccarreta, Silvano Ferrari P46 Smartphone applications (apps) for physical therapists: a review Villanova Luca, Vercelli Stefano P47 A randomized controlled pilot trial of hand robotic training compared with a sensory-motor training program in post stroke patients Violini Claudia, Cenci Marco Joseph, Delconte Carmen, Pisano Fabrizio P48 Critical Illness PolyNeuroMyopathy (CIPNM): chance for a good prognosis Youssef S, Montesano M, Picardi M, De Giampaulis P, Corbo M, Pisani L. P49 The EdUReP approach plus manual therapy for the management of insertional Achilles tendinopathy: a case study Zanetta Anna, Garzonio Fabiola, Ruella Carolina, Sartorio Francesco